Problems of the terminology of legislation regulating ethno-national relations in Ukraine - Kotygorenko V. O.; Panchuk M. I. (Український соціум, 2020)
The article analyzes the problematic aspects of the terminology of legislation regulating ethno-national relations in Ukraine. In particular, these are denotations of the same or identical concepts with different, and in certain cases incorrect words and phrases, lack or inconsistency in the basic definitions. This situation impedes the adoption of a law that would outline the purpose, principles and long-term objectives of the state ethnopolicy and determine the conceptual foundations of further lawmaking, administrative decisions and practical political actions, as well as entails political and legal conflicts. The article substantiates the necessity of implementation of the following definitions of ethnopolitical terms into Ukrainian legislation: state ethno-national policy (state ethnopolicy) of Ukraine – the system of ideas, goals, objectives, principles, legal regulators, state decisions and actions in the field of ethno-national relations; ethno-national relations in Ukraine are relations between individuals, groups of individuals, organizations, institutions and other public entities regarding the consolidation and development of the Ukrainian nation, its historical consciousness, traditions and culture, as well as the development of ethnic, cultural, linguistic and religious distinctive identities of all indigenous peoples and national minorities of Ukraine; Ukrainian nation (Ukrainian people) – citizens of all nationalities who continue the centuries-old history of Ukrainian state building; care of ensuring the human rights and freedoms as well as decent living conditions, of strengthening civil concord on the land of Ukraine; strive to develop and strengthen a democratic, social and rule-of-law Ukrainian state; nationality – a person’s recognition of his/her belonging to a certain group, which is united by similar ideas about its ethnic, cultural, linguistic and religious distinctiveness and by the similarity of civic interests and values, and which has a common historical native name; Ukrainians – persons who are aware of their belonging to the largest ethnically distinctive group in the population of Ukraine, whose historical native name corresponds to the traditional name of the space, which is the territory of the state of Ukraine, as well as persons of all nationalities who are citizens of Ukraine; national minorities of Ukraine include groups of citizens who, being not ethnic Ukrainians, show a sense of national identity and commonality among themselves, maintain long-standing, strong and continuous ties with Ukraine; indigenous peoples of Ukraine are groups of citizens whose sense of national identity and commonality reflect the genesis of these groups in the space that is the territory of the Ukrainian state, where most of the people belonging to these groups live and who are not ethnic Ukrainians.